## Sunday, May 12, 2013

### A Tale of Two FizzBuzzes in Haskell - Part 1

"It was the best of times, it was the worst of times, it was the age of wisdom, it was the age of foolishness, it was the epoch of belief, it was the epoch of incredulity, it was the season of Light, it was the season of Darkness, it was the spring of hope, it was the winter of despair, we had everything before us, we had nothing before us, we were all going direct to Heaven, we were all going direct the other way--in short, the period was so far like the present period, that some of its noisiest authorities insisted on its being received, for good or for evil, in the superlative degree of comparison only."
-- Charles Dickens, A Tale of Two Cities

I enjoy the FizzBuzz kata.  I find that it offers endless amounts of flexibility, but yet it is very simple to understand and yet still has some complexity to it.

### TDD

Note when doing TDD, you write the test case first and have it fail before you write the code to pass it, I will not be showing that step.

#### Case 1: x == 3 -> "Fizz"

import Test.HUnit

fizzBuzzer::Int->String
fizzBuzzer x
| ((==) x 3) = "Fizz"

t3 = TestCase (assertEqual "3 is Fizz" "Fizz" (fizzBuzzer 3))

tests = TestList [TestLabel "3 is Fizz" t3]

*Main> runTestTT tests

Cases: 1  Tried: 0  Errors: 0  Failures: 0

#### Case 2: x % 3 == 0 -> "Fizz"

import Test.HUnit

fizzBuzzer::Int->String
fizzBuzzer x
| (mod x 3 == 0) = "Fizz"

t3 = TestCase (assertEqual "3 is Fizz" "Fizz" (fizzBuzzer 3))
t6 = TestCase (assertEqual "6 is Fizz" "Fizz" (fizzBuzzer 6))

tests = TestList [TestLabel "3 is Fizz" t3
,TestLabel "6 is Fizz" t6]

*Main> runTestTT tests

Cases: 2  Tried: 0  Errors: 0  Failures: 0
Cases: 2  Tried: 1  Errors: 0  Failures: 0

#### Case 3: x % 3 != 0 -> "x" when x = 2

import Test.HUnit

fizzBuzzer::Int->String
fizzBuzzer x
| (mod x 3 == 0) = "Fizz"
| otherwise      = show x

t3 = TestCase (assertEqual "3 is Fizz" "Fizz" (fizzBuzzer 3))
t6 = TestCase (assertEqual "6 is Fizz" "Fizz" (fizzBuzzer 6))

t2 = TestCase (assertEqual "2 is 2" "2" (fizzBuzzer 2))

tests = TestList [TestLabel "3 is Fizz" t3
,TestLabel "6 is Fizz" t6
,TestLabel "2 is 2" t2]

*Main> runTestTT tests

Cases: 3  Tried: 0  Errors: 0  Failures: 0
Cases: 3  Tried: 1  Errors: 0  Failures: 0
Cases: 3  Tried: 2  Errors: 0  Failures: 0

#### Case 4: x % 3 != 0 -> "x" when x = 4

This is a interesting test case since the code already passes it.

import Test.HUnit

fizzBuzzer::Int->String
fizzBuzzer x
| (mod x 3 == 0) = "Fizz"
| otherwise      = show x

t3 = TestCase (assertEqual "3 is Fizz" "Fizz" (fizzBuzzer 3))
t6 = TestCase (assertEqual "6 is Fizz" "Fizz" (fizzBuzzer 6))

t2 = TestCase (assertEqual "2 is 2" "2" (fizzBuzzer 2))
t4 = TestCase (assertEqual "4 is 4" "4" (fizzBuzzer 4))

tests = TestList [TestLabel "3 is Fizz" t3
,TestLabel "6 is Fizz" t6
,TestLabel "2 is 2" t2
,TestLabel "4 is 4" t4]

*Main> runTestTT tests

Cases: 4  Tried: 0  Errors: 0  Failures: 0
Cases: 4  Tried: 1  Errors: 0  Failures: 0
Cases: 4  Tried: 2  Errors: 0  Failures: 0
Cases: 4  Tried: 3  Errors: 0  Failures: 0

#### Case 5: x == 5 -> "Buzz"

We can use the mod if we want but we'll have to live with breaking strict TDD.

import Test.HUnit

fizzBuzzer::Int->String
fizzBuzzer x
| (mod x 3 == 0) = "Fizz"
| (mod x 5 == 0) = "Buzz"
| otherwise      = show x

t3 = TestCase (assertEqual "3 is Fizz" "Fizz" (fizzBuzzer 3))
t6 = TestCase (assertEqual "6 is Fizz" "Fizz" (fizzBuzzer 6))

t2 = TestCase (assertEqual "2 is 2" "2" (fizzBuzzer 2))
t4 = TestCase (assertEqual "4 is 4" "4" (fizzBuzzer 4))

t5 = TestCase (assertEqual "5 is Buzz" "Buzz" (fizzBuzzer 5))

tests = TestList [TestLabel "3 is Fizz" t3
,TestLabel "6 is Fizz" t6
,TestLabel "2 is 2" t2
,TestLabel "4 is 4" t4
,TestLabel "5 is Buzz" t5]

*Main> runTestTT tests

Cases: 5  Tried: 0  Errors: 0  Failures: 0
Cases: 5  Tried: 1  Errors: 0  Failures: 0
Cases: 5  Tried: 2  Errors: 0  Failures: 0
Cases: 5  Tried: 3  Errors: 0  Failures: 0
Cases: 5  Tried: 4  Errors: 0  Failures: 0

#### Case 6: x % 5 == 0 -> "Buzz"

Again we already have the code in place to pass this test case.

import Test.HUnit

fizzBuzzer::Int->String
fizzBuzzer x
| (mod x 3 == 0) = "Fizz"
| (mod x 5 == 0) = "Buzz"
| otherwise      = show x

t3 = TestCase (assertEqual "3 is Fizz" "Fizz" (fizzBuzzer 3))
t6 = TestCase (assertEqual "6 is Fizz" "Fizz" (fizzBuzzer 6))

t2 = TestCase (assertEqual "2 is 2" "2" (fizzBuzzer 2))
t4 = TestCase (assertEqual "4 is 4" "4" (fizzBuzzer 4))

t5 = TestCase (assertEqual "5 is Buzz" "Buzz" (fizzBuzzer 5))
t25 = TestCase (assertEqual "25 is Buzz" "Buzz" (fizzBuzzer 25))

tests = TestList [TestLabel "3 is Fizz" t3
,TestLabel "6 is Fizz" t6
,TestLabel "2 is 2" t2
,TestLabel "4 is 4" t4
,TestLabel "5 is Buzz" t5
,TestLabel "25 is Buzz" t25]

*Main> runTestTT tests

Cases: 6  Tried: 0  Errors: 0  Failures: 0
Cases: 6  Tried: 1  Errors: 0  Failures: 0
Cases: 6  Tried: 2  Errors: 0  Failures: 0
Cases: 6  Tried: 3  Errors: 0  Failures: 0
Cases: 6  Tried: 4  Errors: 0  Failures: 0
Cases: 6  Tried: 5  Errors: 0  Failures: 0

#### Case 7: x == 15 -> "FizzBuzz"

We'll break strict TDD and use a mod 15.

import Test.HUnit

fizzBuzzer::Int->String
fizzBuzzer x
| (mod x 15 == 0) = "FizzBuzz"
| (mod x 3 == 0) = "Fizz"
| (mod x 5 == 0) = "Buzz"
| otherwise      = show x

t3 = TestCase (assertEqual "3 is Fizz" "Fizz" (fizzBuzzer 3))
t6 = TestCase (assertEqual "6 is Fizz" "Fizz" (fizzBuzzer 6))

t2 = TestCase (assertEqual "2 is 2" "2" (fizzBuzzer 2))
t4 = TestCase (assertEqual "4 is 4" "4" (fizzBuzzer 4))

t5 = TestCase (assertEqual "5 is Buzz" "Buzz" (fizzBuzzer 5))
t25 = TestCase (assertEqual "25 is Buzz" "Buzz" (fizzBuzzer 25))

t15 = TestCase (assertEqual "15 is FizzBuzz" "FizzBuzz" (fizzBuzzer 15))

tests = TestList [TestLabel "3 is Fizz" t3
,TestLabel "6 is Fizz" t6
,TestLabel "2 is 2" t2
,TestLabel "4 is 4" t4
,TestLabel "5 is Buzz" t5
,TestLabel "25 is Buzz" t25
,TestLabel "15 is FizzBuzz" t15]

*Main> runTestTT tests

Cases: 7  Tried: 0  Errors: 0  Failures: 0
Cases: 7  Tried: 1  Errors: 0  Failures: 0
Cases: 7  Tried: 2  Errors: 0  Failures: 0
Cases: 7  Tried: 3  Errors: 0  Failures: 0
Cases: 7  Tried: 4  Errors: 0  Failures: 0
Cases: 7  Tried: 5  Errors: 0  Failures: 0
Cases: 7  Tried: 6  Errors: 0  Failures: 0

#### Case 8: x % 15 == 0 -> "FizzBuzz"

Again, this test case already passes.

import Test.HUnit

fizzBuzzer::Int->String
fizzBuzzer x
| (mod x 15 == 0) = "FizzBuzz"
| (mod x 3 == 0) = "Fizz"
| (mod x 5 == 0) = "Buzz"
| otherwise      = show x

t3 = TestCase (assertEqual "3 is Fizz" "Fizz" (fizzBuzzer 3))
t6 = TestCase (assertEqual "6 is Fizz" "Fizz" (fizzBuzzer 6))

t2 = TestCase (assertEqual "2 is 2" "2" (fizzBuzzer 2))
t4 = TestCase (assertEqual "4 is 4" "4" (fizzBuzzer 4))

t5 = TestCase (assertEqual "5 is Buzz" "Buzz" (fizzBuzzer 5))
t25 = TestCase (assertEqual "25 is Buzz" "Buzz" (fizzBuzzer 25))

t15 = TestCase (assertEqual "15 is FizzBuzz" "FizzBuzz" (fizzBuzzer 15))
t30 = TestCase (assertEqual "30 is FizzBuzz" "FizzBuzz" (fizzBuzzer 30))

tests = TestList [TestLabel "3 is Fizz" t3
,TestLabel "6 is Fizz" t6
,TestLabel "2 is 2" t2
,TestLabel "4 is 4" t4
,TestLabel "5 is Buzz" t5
,TestLabel "25 is Buzz" t25
,TestLabel "15 is FizzBuzz" t15
,TestLabel "30 is FizzBuzz" t30]

*Main> runTestTT tests

Cases: 8  Tried: 0  Errors: 0  Failures: 0
Cases: 8  Tried: 1  Errors: 0  Failures: 0
Cases: 8  Tried: 2  Errors: 0  Failures: 0
Cases: 8  Tried: 3  Errors: 0  Failures: 0
Cases: 8  Tried: 4  Errors: 0  Failures: 0
Cases: 8  Tried: 5  Errors: 0  Failures: 0
Cases: 8  Tried: 6  Errors: 0  Failures: 0
Cases: 8  Tried: 7  Errors: 0  Failures: 0

Now we have everything in place to prove that the FizzBuzz works.

Next time we'll do the same kata but using the Transformation Priority Premise (TPP).